Prospective Study of Plasmodium vivax Malaria Recurrence after Radical Treatment with a Chloroquine-Primaquine Standard Regimen in Turbo, Colombia (2016)
ABSTRACT: Plasmodium vivax recurrences help maintain malaria transmission. They are caused by recrudescence, reinfection, or relapse, which are not easily differentiated. A longitudinal observational study took place in Turbo municipality, Colombia. Participants with uncomplicated P. vivax infection received supervised treatment concomitantly with 25 mg/kg chloroquine and 0.25 mg/kg/ day primaquine for 14 days. Incidence of recurrence was assessed over 180 days. Samples were genotyped, and origins of recurrences were established. A total of 134 participants were enrolled between February 2012 and July 2013, and 87 were followed for 180 days, during which 29 recurrences were detected. The cumulative incidence of first recurrence was 24.1% (21/87) (95% confidence interval [CI], 14.6 to 33.7%), and 86% (18/21) of these events occurred between days 51 and 110. High genetic diversity of P. vivax strains was found, and 12.5% (16/128) of the infections were polyclonal. Among detected recurrences, 93.1% (27/29) of strains were genotyped as genetically identical to the strain from the previous infection episode, and 65.5% (19/29) of infections were classified as relapses. Our results indicate that there is a high incidence of P. vivax malaria recurrence after treatment in Turbo municipality, Colombia, and that a large majority of these episodes are likely relapses from the previous infection. We attribute this to the primaquine regimen currently used in Colombia, which may be insufficient to eliminate hypnozoites.